1991
DOI: 10.1002/j.1460-2075.1991.tb04954.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic shuttling of the progesterone receptor.

Abstract: The nuclear localization of the progesterone receptor is mediated by two signal sequences: one is constitutive and lies in the hinge region (between the DNA and steroid binding domains), the other is hormone dependent and is localized in the second zinc finger of the DNA binding domain. The use of various inhibitors of energy synthesis in cells expressing permanently or transiently the wild‐type receptor or a receptor mutated within the nuclear localization signals, demonstrated that the nuclear residency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
151
1
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(163 citation statements)
references
References 55 publications
8
151
1
2
Order By: Relevance
“…Another region that is important for nuclear localization (NLS2) is located in the second Zinc finger in the DNA binding domain of nuclear receptors such as orphan nuclear receptor TR2 [Yu et al, 1998] and PR [Guiochon-Mantel et al, 1991;Ylikomi et al, 1992]. Analogous sequences exist in the RXR as well as in LXR a and LXR b.…”
Section: Mutations In Nls1 and Nls2 Abolish Nuclearmentioning
confidence: 99%
See 3 more Smart Citations
“…Another region that is important for nuclear localization (NLS2) is located in the second Zinc finger in the DNA binding domain of nuclear receptors such as orphan nuclear receptor TR2 [Yu et al, 1998] and PR [Guiochon-Mantel et al, 1991;Ylikomi et al, 1992]. Analogous sequences exist in the RXR as well as in LXR a and LXR b.…”
Section: Mutations In Nls1 and Nls2 Abolish Nuclearmentioning
confidence: 99%
“…Export from the nucleus occurs through receptormediated mechanisms. Studies using heterokaryon and imaging experiments showed that exported nuclear receptors are reimported into the nucleus [Guiochon-Mantel et al, 1991;Hache et al, 1999;Prufer and Barsony, 2002]. It is well established that nuclear receptors are imported into the nucleus by karyopherins.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although specific nuclear export signals have been recently identified in a few proteins [27][28][29], there is also evidence arguing for nuclear export by a default pathway [30,31]. At present experimental evidence is lacking which could show whether Vigilin shuttles continuously across the nuclear envelope like some nucleolar proteins [32], the progesterone receptor [33] or some of the hnRNPs [27], or is stably anchored at the ER after it had passed by the nucleus.…”
Section: Vigilin Is Present Both In the Cytoplasm And In The Nucleusmentioning
confidence: 99%